Mechanical behaviour and fracture mechanism of coal mine roadway surrounding rock considering seepage field - Zhao, Shujie; Chen, Yian; Xu, Wensong; Xu, Jiang; Cheng, Xiang (Frontiers in Materials, 2025)
During the exploitation of deep coal resources, groundwater significantly compromises the stability of the surrounding rock in coal mine roadway. To investigate the effect of seepage fields on the mechanical behaviour and fracture mechanism of coal mine roadway surrounding rock, a series of conventional triaxial compression tests is conducted under various seepage fields. The results indicate that the peak stress of rock decreases linearly under top seepage pressure, with a reduction gradient of 2.20 MPa/MPa. In contrast, the peak stress declines nonlinearly under the condition of bottom seepage pressure, with the rate of reduction decreasing as bottom seepage pressure decreases. Both top and bottom seepage pressures significantly impact rock permeability by influencing pore pressure and seepage pressure differences. During the progressive failure process, the axial strain field transitions from a layered to a concentrated distribution, demonstrating deformation localisation. The primary fracture extends from one edge of the specimen to the opposite edge, suggesting that accumulated bottom seepage pressure induces stress concentration at the end face of specimen. Additionally, secondary cracks adjacent to the primary fracture result from pore pressure effects. A key distinction between unilateral and bilateral seepage pressure is the shift in fracture mode of rock: from a mixed transgranular and intergranular fracture pattern to one dominated by intergranular fracture. The research findings provide a theoretical basis for the design of advanced support systems and the stability analysis of deep coal mine roadways affected by groundwater.